Upaya Mengembangkan Usaha Mikro Kecil Menengah (UMKM) Dengan Pembuatan Donat Kentang Di Lingkungan V Kelurahan Tanah Seribu, Kota Binjai - Sri Hari Yanti; Septi Ardianti; Reni Purnama Sari; Rindi Fatmawati; Ella Andhany (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
This study aims to analyze efforts to develop Micro, Small and Medium Enterprises (MSMEs) by making potato donuts in Neighborhood V, Tanah Seribu village, Binjai City. This research focuses on developing and increasing sales of Potato Donut products made by local mothers. Efforts to develop and increase sales are an important aspect in the development of the Potato Donut business. An effective marketing strategy will play a role in influencing consumer interest in buying Potato Donut products. Therefore, a good marketing strategy analysis is needed to increase the number of donut product sales. This type of research is qualitative research. It is research that tries to describe and interpret something. The data sources used in this research are primary data, secondary data. The data analysis technique in this study uses an interactive analysis model. With the potato donut business, the community can have an alternative source of income that can help improve the family's economic condition.